Syringomyelia and the fluid-structure interactions of a cerebrospinal waveguide - Elliott, N.; Lucey, Anthony; Lockerby, D.; Brodbelt, A. (2014)
In the disease syringomyelia, fluid-filled cavities, called syrinxes, form in the spinal cord. The expansion of these pathological pressure vessels compresses the surrounding nerve fibers and blood supply, which is associated with neurological damage. We investigate the spinal wave-propagation characteristics, principally to serve as a reference for more anatomically-detailed models. The spinal cord is modeled as an elastic cylinder, which becomes an annulus containing inviscid fluid when a syrinx is included. This is surrounded by an annulus of in-viscid fluid, representing the cerebrospinal fluid occupying the subarachnoid space, with an outer rigid boundary approximating the dura mater. The axisymmetric harmonic motion is solved as an eigenvalue problem. We present dispersion diagrams and describe the physical mechanism of each wave mode. We identify potentially damaging syrinx fluid motions and tissue stress concentrations from the eigenvectors. Finally, we determine the dependence of each wave mode on syrinx radius and cord tissue compressibility.